1976
DOI: 10.2307/3897686
|View full text |Cite
|
Sign up to set email alerts
|

Range Improvement Practices and Ferruginous Hawks

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 10 publications
2
31
0
Order By: Relevance
“…During the nestling period in Alberta, ferruginous hawks relied primarily (89 % of biomass) on sciurid rodents (Schmutz et al 1980); lagomorph prey is of primary importance elsewhere (Howard and Wolfe 1976;Smith and Murphy Sociobiology 1978). Densities of breeding ferruginous hawks already have been shown to fluctuate in concert with the abundance of black-tailed jackrabbits (Lepus californicus) in Utah (Smith et al 1981).…”
Section: Introductionmentioning
confidence: 99%
“…During the nestling period in Alberta, ferruginous hawks relied primarily (89 % of biomass) on sciurid rodents (Schmutz et al 1980); lagomorph prey is of primary importance elsewhere (Howard and Wolfe 1976;Smith and Murphy Sociobiology 1978). Densities of breeding ferruginous hawks already have been shown to fluctuate in concert with the abundance of black-tailed jackrabbits (Lepus californicus) in Utah (Smith et al 1981).…”
Section: Introductionmentioning
confidence: 99%
“…However, Howard and Wolfe (1976) found that conversion of shrubland to crested wheatgrass did not adversely affect ferruginous hawk reproduction in Idaho and Utah. Instead, ferruginous hawks were able to exploit different prey in seeded grasslands compared to native desert shrub habitats in their study.…”
Section: Land Conversion From Shrubland To Grasslandmentioning
confidence: 87%
“…However, above 30 percent cultivation, ferruginous hawk density declined, as did the abundance of ground squirrels, the primary prey species on the study area. Several other researchers have reported a negative relationship between breeding ferruginous hawks and cultivation; only 1 percent of nests in Idaho and Utah had traces of cultivated land in the vicinity (Howard 1975, Howard andWolfe 1976), and only 3 percent of nests in South Dakota were on cultivated land (Blair 1978). Similarly, only 2 percent of ferruginous hawk nests in Oregon were on cultivated lands, much less than expected based on availability (Cottrell 1981).…”
Section: Land Conversion To Agriculturementioning
confidence: 99%
See 2 more Smart Citations